2022
DOI: 10.1186/s12916-022-02584-x
|View full text |Cite
|
Sign up to set email alerts
|

Speech silence character as a diagnostic biomarker of early cognitive decline and its functional mechanism: a multicenter cross-sectional cohort study

Abstract: Background Language deficits frequently occur during the prodromal stages of Alzheimer’s disease (AD). However, the characteristics of linguistic impairment and its underlying mechanism(s) remain to be explored for the early diagnosis of AD. Methods The percentage of silence duration (PSD) of 324 subjects was analyzed, including patients with AD, amnestic mild cognitive impairment (aMCI), and normal controls (NC) recruited from the China multi-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In Mazzeo et al ( 2022 ), researchers observed associations between disease progression, language lesions, and brain hypometabolism. In addition, evidence shows that MCI patients show longer speech and phonation time (Tóth et al, 2018 ; Gosztolya et al, 2019 ), an incremented length of silent pauses (voiceless) (Wang et al, 2022 ), lower speech rate (Tóth et al, 2018 ), presence of stammers and articulatory disfluencies that interrupt speech with longer hesitations (López-de Ipiña et al, 2013 ; Tóth et al, 2018 ), and impairments in formant features in phonological planning formants (Themistocleous et al, 2018 ). For a more detailed description of these alterations, (see Martínez-Nicolás et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mazzeo et al ( 2022 ), researchers observed associations between disease progression, language lesions, and brain hypometabolism. In addition, evidence shows that MCI patients show longer speech and phonation time (Tóth et al, 2018 ; Gosztolya et al, 2019 ), an incremented length of silent pauses (voiceless) (Wang et al, 2022 ), lower speech rate (Tóth et al, 2018 ), presence of stammers and articulatory disfluencies that interrupt speech with longer hesitations (López-de Ipiña et al, 2013 ; Tóth et al, 2018 ), and impairments in formant features in phonological planning formants (Themistocleous et al, 2018 ). For a more detailed description of these alterations, (see Martínez-Nicolás et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, several voice parameters were identified as the most discriminatory using ML approaches for differentiating MCI with positive and negative amyloid status. Among the most important voice parameters identified ( Figure 4 ), there were spectral features (relative energy in different frequency bands), associated with vocal emotional expre ssions Sauter et al ( 2010 ), voiced segments (the portion of speech with relatively constant phonetic features) useful to differentiate AD from healthy individuals (López-de Ipiña et al, 2013 ; Wang et al, 2022 ), and measures of the Hammarberg index, a spectral measure of voice quality, which has been identified as a discriminant feature for MCI (Themistocleous et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Pitt centre cohort, PSD was verified as a reliable marker to differentiate mild AD from normal controls. 49…”
Section: General Psychiatrymentioning
confidence: 99%
“…Language functioning can provide valuable insights into cognition and behavior, serving as a window into an individual's cognitive functioning [7][8][9][10][11][12]. Speech and language offer an opportunity to use ecologically valid methods to assess key symptoms related to cognitive function, a unique advantage in the assessment and monitoring of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%